Nuclear erythroid 2‐related factor 2 activation inhibits house dust mite–induced sinonasal epithelial cell barrier dysfunction. Issue 5 (2nd February 2017) - London, Nyall R.; Tharakan, Anuj; Lane, Andrew P.; Biswal, Shyam; Ramanathan, Murugappan
Abstract : Background: Dysregulated sinonasal epithelial cell (SNEC) barrier function has been proposed to contribute to the pathogenesis of sinonasal inflammatory conditions such as allergic rhinitis (AR) and chronic rhinosinusitis (CRS). Allergens such as house dust mite (HDM) have been reported to disrupt SNEC barrier integrity. We have recently identified nuclear erythroid 2‐related factor 2 (Nrf2) activation via sulforaphane (SFN) stimulation to stabilize SNEC barrier function. The purpose of this study was to explore whether Nrf2 activation could ameliorate HDM‐induced SNEC barrier dysfunction. Methods: Human SNECs (HSNECs) were grown from patients at the air‐liquid interface (ALI). HSNECs were stimulated with HDM with or without pharmacologic activation of Nrf2 with SFN. HSNECs were then stained for the epithelial cell junction protein zonula occludens‐1 (ZO‐1) and cell surface localization was evaluated by confocal microscopy. Transepithelial electrical resistance (TER) and paracellular fluorescein isothiocyanate (FITC)‐dextran permeability was measured in response to stimulation with HDM and SFN. Results: HDM stimulation caused a global disruption of the protein ZO‐1 along with an associated decrease in TER ( p < 0.001) and increased FITC‐dextran paracellular permeability ( p < 0.0001). Enhancing Nrf2 activation through treatment with SFN prior to stimulation with HDM was associated with increased localization of ZO‐1 at the cell surface and statistically significant increases in TER ( p < 0.05) and decrease in paracellular FITC‐dextran permeability ( p < 0.001). Conclusion: This is the first study to demonstrate that HDM‐induced SNEC barrier dysfunction may be preventable by Nrf2 activation. The Nrf2 antioxidant pathway may represent a potential therapeutic target for allergen‐induced sinonasal inflammation.